Numerical Simulation of Wire Rod Cooling in Eutectoid Steel under Forced-Convection - Monserrat Sofía López-Cornejo; Héctor Javier Vergara-Hernández; Sixtos Antonio Arreola-Villa; Octavio Vázquez-Gómez; Martín Herrejón-Escutia (Metals, 2021)
A coupled thermal-microstructural simulation model was developed to estimate the thermal history in a eutectoid steel wire rod under continuous cooling and forced-convection. The model coupled the phenomena of heat transfer, phase transformation and estimation of the cooling boundary condition. The thermal histories were analyzed at different cooling rates to emulate the forced-convection conditions by air-jet as in the controlled cooling conveyor. The thermal histories were acquired and used to calculate the forced-convection heat transfer coefficients through the solution of the Inverse Heat Conduction Problem, while the phase transformation was approximated with the Johnson–Mehl–Avrami–Kolmogorov (JMAK) kinetic model. From the heat transfer coefficients and the kinetic parameters, a user-defined function (UDF) was coded and employed in the ANSYS Fluent® software. The model results were compared and validated with the experimental histories, obtaining a good agreement between both responses, while the microstructural evolution of the pearlite was validated using Scanning Electron Microscopy (SEM) and Vickers microhardness. It was found that specimen diameter and air velocity are the main variables to modify the undercooling and therefore the pearlite interlamellar spacing.